Avaliaç\~ao de eficiência em sistemas de saúde: Brasil, América Latina, Caribe e OCDE - Alexandre Marinho; Simone de Souza Cardoso; Vivian Vicente de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This work follows the series of studies conducted in Ipea, in order to compare the efficiency of the Brazilian health system to health systems of other countries. We evaluate the efficiency of expenditure in health care provision by comparing various output measures (life expectancy; infant survival rate; years of life recovered from diseases; population; area) from the health system of Brazil, Latina America, Caribbean Countries and Organisation for Economic Co-operation and Development (OECD) countries with an expenditure measure (health expenditure per capita). In short, we have merged the two databases of our antecedent works. When estimating the efficiency frontier and country rankings we combine data envelopment analysis (DEA) with stochastic frontiers (SFs). We show that the results we have for Brazil and other countries tend to differ, sometimes substantially, depending on the methods and samples used. We believe that much caution is required when performing efficiency analysis across countries. This question is still open in the literature.
Keywords: C61; D61; H51; I12; I18; 330; compared health systems; stochastic frontier analysis; data envelopment analysis